Effect Of Patient Safety Implementation And Marketing Mix On Outpatient Re-Visiting Interest Of Patients With Patient Trust As An Intervening Variable - Jhon perry B Simanjuntak; Andry Andry; Kemala Rita Wahidi (Jurnal Health Sains, 2022)
The number of hospitals that stand is a necessity of a form of competition in the field of the health industry. this also affects patients in determining the choice of a place for health services. the interest in patient re-visits can be determined by the factors of implementing patient safety and marketing mix. research objectives: this study aims to analyze the effect of the implementation of patient safety and marketing mix on the interest in re-visiting patients in outpatient hospital 'x' with variables intervening patient confidence. research method: quantitative explanatory because it is to know the relationship between variables that are based on the research hypothesis. the samples in this study used the hair formula, namely (5-10) x n. the number of samples is (5) x 36, so 180sampel will be taken. the analysis technique uses structural equation modelling (sem). results of the study: the implementation of patient safety and marketing mix had a significant effect on patient confidence and interest in re-visiting. trust also significantly affects the patient's re-visiting interest. in addition, this study found that patient confidence mediated the effect of applying patient safety and marketing mix on patient re-visiting interest at "x" hospital bekasi.